2009
DOI: 10.1002/ejic.200900652
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Linear Tetranuclear Silver(I) Complexes Bridged by Tetraphosphane Ligands

Abstract: Reactions of AgOTf with meso-bis [(diphenylphosphanylmethyl)phenylphosphanyl]methane (dpmppm) afforded [Ag 4 (OTf) 2 (µ-OTf)(µ-dpmppm) 2 {(CH 3 ) 2 CO}](OTf) (1) and [Ag 4 (OTf) 2 (µ-OTf)(µ-dpmppm) 2 (RNC) 2 ](OTf) {R = Xyl (2a), Mes (2b), tBu (2c)}. When AgOTf was treated with dpmppm in air in the presence of tBuNC, cleavage of the C-Cl and P-C bonds occurred to give [Ag 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The flexible Au I 4 chain was further converted into the cyclic Au I 6 complex, [Au 6 Cl 4 (µ‐ meso ‐dpmppm) 2 ] 2+ and the linear Au I 8 complex, [Au 8 (µ‐I) 2 (µ 3 ‐I) 2 (µ‐ meso ‐dpmppm) 4 ] 4+ . Similar M 4 bridging mode of meso ‐dpmppm was observed in syn ‐ and anti ‐arrangements of linear Ag I 4 chains, syn ‐arrangement of Cu I 4 units, {Cu 4 (µ‐X) 3 (µ‐dpmppm) 2 } + , and ladder‐type Cu I 8 complexes, [Cu 8 (µ‐X) 2 (µ 3 ‐X) 6 (µ‐dpmppm) 2 ] (X = Cl, Br, I) . The M 4 flexible bridge of meso ‐dpmppm also accommodated octanuclear rings of [{Au 2 MCuCl 2 (µ‐ meso ‐dpmppm) 2 } 2 ] 4+ (M = Au, Ag, Cu), which incorporate a BF 4 – or PF 6 – counter anion into the metal ring …”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The flexible Au I 4 chain was further converted into the cyclic Au I 6 complex, [Au 6 Cl 4 (µ‐ meso ‐dpmppm) 2 ] 2+ and the linear Au I 8 complex, [Au 8 (µ‐I) 2 (µ 3 ‐I) 2 (µ‐ meso ‐dpmppm) 4 ] 4+ . Similar M 4 bridging mode of meso ‐dpmppm was observed in syn ‐ and anti ‐arrangements of linear Ag I 4 chains, syn ‐arrangement of Cu I 4 units, {Cu 4 (µ‐X) 3 (µ‐dpmppm) 2 } + , and ladder‐type Cu I 8 complexes, [Cu 8 (µ‐X) 2 (µ 3 ‐X) 6 (µ‐dpmppm) 2 ] (X = Cl, Br, I) . The M 4 flexible bridge of meso ‐dpmppm also accommodated octanuclear rings of [{Au 2 MCuCl 2 (µ‐ meso ‐dpmppm) 2 } 2 ] 4+ (M = Au, Ag, Cu), which incorporate a BF 4 – or PF 6 – counter anion into the metal ring …”
Section: Introductionmentioning
confidence: 87%
“…Multinuclear transition‐metal complexes have extensively been studied to explore new aspects of functional materials because a variety of synergistic effects in multimetallic centers are expected to play key roles in developing catalytic systems, electronic, optical, and magnetic devices, and biomimetic functional molecules . To create desired multinuclear centers, design of multidentate metal supporting ligands is very important issue, and in this regard, we have prepared a methylene‐bridged linear tetraphosphane, meso ‐ and rac ‐bis[(diphenylphosphinomethyl)phenylphosphino]methane (dpmppm), and demonstrated that it effectively stabilized versatile tetra‐, tri‐, and dinuclear homo and heterometallic systems as well as mononuclear centers (Scheme ) . First of all, meso ‐ and rac ‐dpmppm preferably supported linearly ordered tetranuclear metal centers in κ 1 ,κ 1 ,κ 1 ,κ 1 coordination mode (Scheme a, Scheme f), exemplified by the linear octapalladium rigid‐rods, [Pd 8 ( meso ‐ or rac ‐dpmppm) 4 L 2 ] 4+ (L = none, MeCN, N , N ‐dimethylformamide (dmf), and isocyanides),, which dissociate at higher temperature T > 100 °C into two tetrapalladium units of {Pd 4 ( meso ‐ or rac ‐dpmppm) 2 } 2+ and interestingly they are self‐aligned at lower temperature T < 60 °C to restore the original rods through asymmetric recognition between the tetrapalladium units .…”
Section: Introductionmentioning
confidence: 99%
“…Related metal exchange reactions have been previously observed with heterometallic chains doubly supported by P,C NHC ,P ligands (see Schemes 23 and 26 in section 3.7). 282 With the P4 ligands, tetranuclear copper 73,348 and silver 75,349 chains displaying metallophilic interactions were characterized. 74 In heterotrinuclear Ag−Pt−Ag chains supported by one P4 ligand, the two internal P donors chelate the Pt center and each Ag−Pt bond is further bridged by an acetylide ligand.…”
Section: Pnnp Donor Atomsmentioning
confidence: 99%
“…With the P4 ligands, tetranuclear copper , and silver , chains displaying metallophilic interactions were characterized . In heterotrinuclear Ag–Pt–Ag chains supported by one P4 ligand, the two internal P donors chelate the Pt center and each Ag–Pt bond is further bridged by an acetylide ligand.…”
Section: Tetradentate “Short-bite” Ligandsmentioning
confidence: 99%